Effectiveness of the Capture the Fracture Program for Patients with Hip Fractures at Phrae Hospital: A 2-Year Follow-up After Surgery - Tungtrongjit, Yodpiti; Wiengkum, Pattira; Pongpan, Surangrat (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: To determine the effectiveness of the Capture the Fracture (CTF) program in preventing refractures, improving Barthel index scores for activities of daily living (ADL), and reducing mortality rates in patients with hip fractures. Methods: This study enrolled patients with fragile hip fractures aged ≥50 years who underwent hip fracture surgery. The participants were classified into the intervention and control groups, each consisting of 46 patients. The intervention group underwent the CTF program with a multifactorial approach, whereas the control group received routine care. Participants were followed up 1 and 2 years postoperatively to assess outcomes, including the Timed Up and Go test, balance test, Barthel index scores for ADL, fall risk assessment, refracture, and mortality rate. Results: In the intervention group, no recurrent fractures occurred within 1 year, compared to 6.5% in the control group (p=0.106). At the 2-year postoperative follow-up, 4.9% of the intervention group experienced recurrent fractures, whereas the control group had no fractures (p=0.508). The 2-year postoperative mortality rate was 18.0% and 37.0% in the intervention and control groups, respectively (p=0.042). Conclusions: Multidisciplinary teams should implement the CTF program using a multifactorial approach to physical rehabilitation in patients with hip fractures. This program improved participants' quality of life and reduced the mortality rate 2 years postoperatively.